MENINGKATKAN KEMANDIRIAN ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN PERAN - Elis, Berita Mambarasi Nehe, Yusdiana (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This study aims to increase child independence through role play in group B children in PAUD al-Hidayah. This type of  research is class action research (PTK). The action model used in this study used Kemmis & Mc techniques.  Taggart. It consists of four components: (1) planning (2) action (3) observation and (4) reflection. The subject of this  study was group B students aged 5-6 years in PAUD al-Hidayah District Tunjung Teja which had 13 children  consisting of 6 girls 7 boys. Tekhnik data collection is carried out by means of Observation, Interview, and  Documentation. The research is carried out in 2 cycles, each of which is in the form of planning, execution, results of  observations and reflection. This study was carried out with collaboration between teachers and researchers. From the  results of the study it was shown that role-playing can increase the independence of the child this is evident from the  results of observation before the action and after the action. It is evident from the results of child independence in the  pre cycle 62.88% and the cycle I increase in child independence 77.50% and the second cycle the increase in child  independence reached 77.50% and has met the average percentage that has been targeted. Based on the research, it  can be concluded that through role-playing methods it can improve the independence ability of PAUD al-Hidayah  children of Tunjung Teja District.